2012
DOI: 10.1103/physrevc.85.041602
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry breaking and fluctuations within stochastic mean-field dynamics: Importance of initial quantum fluctuations

Abstract: Dynamics of spontaneous symmetry breaking and fluctuations in the Lipkin-Meshkov-Glick model are investigated in a stochastic mean-field approach. Different from the standard mean-field, in the stochastic approach, initial state fluctuations, are incorporated. In weak coupling, the approach perfectly reproduces the exact quantal dynamics. On the other hand, for increasing coupling strength, above the symmetry breaking threshold, the approach provides description of gross properties (i.e. time averaged behavior… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
52
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 31 publications
0
52
1
Order By: Relevance
“…In nuclear physics this approach, called stochastic mean field [36], has been originally introduced such that initial fluctuations in collective space are reproduced through arXiv:1609.01424v2 [nucl-th] 21 Mar 2017 fluctuations of the initial one-body density. In a series of works, it was shown that it surprisingly well accounts for correlations beyond mean-field [37][38][39] while treating properly the dynamic close to a spontaneous symmetry breaking [38]. It is also able to include approximately many-body correlation to all orders by connecting the evolution to the BBGKY hierarchy [40].…”
mentioning
confidence: 99%
“…In nuclear physics this approach, called stochastic mean field [36], has been originally introduced such that initial fluctuations in collective space are reproduced through arXiv:1609.01424v2 [nucl-th] 21 Mar 2017 fluctuations of the initial one-body density. In a series of works, it was shown that it surprisingly well accounts for correlations beyond mean-field [37][38][39] while treating properly the dynamic close to a spontaneous symmetry breaking [38]. It is also able to include approximately many-body correlation to all orders by connecting the evolution to the BBGKY hierarchy [40].…”
mentioning
confidence: 99%
“…These transport coefficients have similar form with those that are familiar from phenomenological nucleon exchange model [16], but provide a more refined description for transport mechanism. In a recent application, the SMF approach is tested with Lipkin-Meshkov-Glick model, and it is found that the gross properties of the model are well produced in the SMF approach [17]. The SMF approach was also extended by including pairing interaction [18].…”
Section: Introductionmentioning
confidence: 99%
“…x (t), σ 2 y (t) and ∆ 2 z (t), respectively. In each case, results of the SMF simulations are shown with triangles (σ 2 x ), squares (σ 2 y ) and circles (σ 2 z ) (taken from [3]). …”
Section: Many-body Dynamics Near a Saddle Pointmentioning
confidence: 99%
“…Starting from the statistical properties (6) and (7), it could be shown that the quasi-spins should be initially sampled according to Gaussian probabilities with first moments given by [3] …”
Section: Many-body Dynamics Near a Saddle Pointmentioning
confidence: 99%
See 1 more Smart Citation